Study about Caecal Volvulus in East Africa: A Rare Cause of Bowel Obstruction - Richard Wismayer (Current Practice in Medical Science Vol. 10, 2022)
Caecal volvulus is a rare cause of adult bowel obstruction characterised by torsion of the caecum and terminal ileum around the mesentery. Caecal volvulus happens to be the second most common form of large bowel volvulus after sigmoid volvulus. The goal of this review is to raise surgeon awareness of this type of bowel obstruction through a patient case discussion and treatment strategies for caecal volvulus. A 47 year old gentleman had an emergency laparotomy for large bowel obstruction following preoperative resuscitation. There was axial rotation of the caecum with congestion of the caecum’s posterior wall during laparotomy. An end-to-end ileo-transverse anastomosis and right hemicolectomy were performed, and the recovery period was uneventful. The clinical presentation is quite varied and can range from colicky abdominal pain that comes and goes to generalised abdominal pain brought on by intestinal gangrene and sepsis. Caecal volvulus carries a significant mortality rate, particularly if the preoperative diagnosis is delayed. When a strong index of suspicion is taken into account for early diagnosis to avoid intestinal ischaemia and ultimately gangrene and sepsis, this mortality may be decreased.